Graphic Reading Performance of Students with Visual Impairments and Its Implication for Instruction and Assessment. (May 2021) - Zebehazy, Kim T.; Wilton, Adam P.
Introduction: The ability of students to engage with graphical materials supports learning in science, technology, engineering, arts, and mathematics areas. For students with visual impairments, understanding the factors that contribute to the effective interpretation of graphics can promote meaningful access to the curricula. Methods: Forty students with visual impairments completed multiple-choice question tasks for five types of graphics presented in their medium of choice and provided difficulty ratings. The teachers of students with visual impairments rated the students on several factors. Statistical analyses investigated the relationship between performance differences and teacher-rated factors. Results: Significant differences in performance between print and tactile graphics users were found for bar graph, map, and total correct responses on all tasks. For some tasks, perceived difficulty by tactile graphic users did not align with actual performance. Teachers' ratings of students who had Individualized Education Program goals for graphics, independence in using graphics, problem-solving ability, mathematics ability, and frequency of engaging with graphics contributed to significant differences in performance across total correct and most individual graphic results. Discussion: Although medium type was a significant contributor across graphic types, some teacher-rated variables appeared to mitigate the importance of medium on student performance. Depending on the graphic type, experience, content knowledge, skills with graphics, and confidence and motivation can all affect student performance when interpreting graphics. Implications for practitioners: Teachers should provide students with early and frequent opportunities to engage with graphics and support their problem-solving abilities regarding how to engage with different graphic types to enhance their independent use of graphics.